21st Century Learning: A Research Analysis of Numeracy Literacy Trends among Students - Novi Nityasanti; Alfi Laila; Amara Saida; Baharudin Baharudin; Mohd Hanafi Mohd Yasin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study analyzes recent trends in numeracy literacy among primary school students in Kediri District and identifies the challenges, opportunities, and steps to improve students' numeracy achievement in the 21st century. Method: A qualitative approach was used in this study, including interviews with teachers, classroom observations, and documentation of numeracy assessment results. The study involved 200 grade 4 and 5 students from 10 partner primary schools in the Campus on Duty (CoD) program. Results: The findings indicate that numeracy literacy trends are influenced by the integration of technology, including game-based learning applications and online platforms. Despite limited resources and insufficient teacher training, technology provides significant opportunities for enhancing numeracy learning. Project-based learning and collaboration with local technology communities were found to be effective in improving numeracy understanding by allowing students to apply concepts in real-world contexts. Novelty: This study emphasizes the unique role of project-based learning and collaboration with local technology communities as strategies for improving numeracy literacy. By integrating real-world contexts and technology, the findings offer new insights into bridging traditional teaching methods with innovative approaches, addressing the evolving demands of 21st-century education.